Analysis of Factors Affecting Exclusive Breastfeeding in Primipara Mother - Wahyu Utami Ekasari; Dewi Sapta Wati (LPPM AN NUUR, 2021)
Background: Exclusive breastfeeding in the world is still low. Based on data from the United Nations Children's Fund (UNICEF) in 2021, only 39% of babies under 6 months of age are exclusively breastfed worldwide. Exclusive breastfeeding is influenced by several factors, namely presdisposing factors; Enabling factors and reinforcement factors Purpose: to determine the relationship between maternal education level, family income, and family support for exclusive breastfeeding for primiparous mothers Methods: Analytical survey with a retrospective approach, The number of samples in this study were 63 respondents. Bivariate analysis using the Chi Square test. Results: From 63 respondents, that there was a relationship between education level (p - value 0.008) and family support (p - value 0.033) with exclusive breastfeeding and there was no relationship between family income (p = value 0.625) and breastfeeding. exclusive. Conclusion: there was a relationship between the level of education and family support with exclusive breastfeeding and there was no relationship between family income and exclusive breastfeeding.